The influence of resisted exercises on the balance, functional mobility and in the elderly’s quality of life - Ralfe Aparício do Prado; Andréa Lemos Castilho Teixeira; Cátia Juliana Samuel Oliveira Langa; Paula Regina Maria Egydio; Paola Izzo (O Mundo da Saúde)
Old people show clear decreases of force, muscle endurance, movement speed and power. Even in normal aging, one observes significant losses of force and muscle mass predominant in lower members and closely related to less physical activity. There is a decline in individuals’ independence, with the reduction of lower members muscle force and higher risks of falls and a extremely high probability of instability or immobility able to influence old people autonomy, well-being and quality of life. The aim of this work was to evaluate balance, functional mobility and quality of life of old people engaged in a program of resisted exercises. 4 old individuals with an average age of 70.25 + 8.61 years were submitted to a program of resisted exercises during 5 weeks, being evaluated before and after the intervention using Berg Balance Scale, Timed Up and Go (TUG) test and WHOQOL - BREF. It was verified that all old subjects increased the degree of force in up to 200%, and subjects 1 and 3 improved their balance in 3.92% and 3.70% respectively, 1 and 4 reduced the time for doing TUG in 14% and 12.28% respectively, 2 and 4 had a 4.54% and 6.25%, respectively, improvement in the physical domain of quality of life, and all improved the psychological domain in up to 71.42%, but only one had improvements in the social and environmental domains. One concluded that the program of resisted exercises used in this study was efficient in the increase of balance, functional mobility and physical and psychological domains of quality of life of the old subjects, although without much impact in the social and environmental domains.